To solve the equation \(24 = x^2 - 4x + 3\), we start by moving all terms to one side:
\[ x^2 - 4x + 3 - 24 = 0 \]
Simplifying gives:
\[ x^2 - 4x - 21 = 0 \]
Next, we will complete the square for the quadratic expression \(x^2 - 4x\). The process involves taking the coefficient of \(x\), which is \(-4\), halving it to get \(-2\), and then squaring it to find \(4\). Let's rewrite the equation:
- Rewrite:
\[ x^2 - 4x = (x - 2)^2 - 4 \]
Now we can substitute this back into our equation:
\[ (x - 2)^2 - 4 - 21 = 0 \]
Combining the constants gives:
\[ (x - 2)^2 - 25 = 0 \]
Next, we can reorganize the equation to be in the form \((x - c)^2 = d\):
\[ (x - 2)^2 = 25 \]
- Now, we solve for \(x\):
Taking the square root of both sides:
\[ x - 2 = \pm 5 \]
This gives us two equations to solve:
\[ x - 2 = 5 \quad \text{or} \quad x - 2 = -5 \]
Solving these:
- For \(x - 2 = 5\):
\[ x = 5 + 2 = 7 \]
- For \(x - 2 = -5\):
\[ x = -5 + 2 = -3 \]
Thus, the solutions are:
\[ x = 2 \pm 5 \]
From the options provided, the correct choice is:
(Choice A) \(x=2 \pm 5\).